Методологічні основи дослідження лідерської компетентності майбутніх офіцерів у ВВНЗ - Бойко, Олег (Видавництво Львівської політехніки, 2012)
В статье рассматриваются методологические основы исследования лидерской компетентности будущих офицеров в процессе их подготовки в военных высших учебных заведениях. Автор дает определение понятия “лидерская компетентность” на основе системно-деятельностного подхода. The article considers methodological principles of research of future officers’ leader competence in the process of their preparation in military educational establishments. Basing on the analysis of system and activity approach, the author deduces the definition of the concept of “leader competence”.
Методологические основы исследования лидерской компетентности будущих офицеров в военных вузах
Methodological principles of research of future officers’ leader competence in military educational establishments
Keywords: профессиональная компетентность; лидерство офицера; лидерская компетентность; professional competence; leadership of an officer; leader competence